PENCITRAAN KAWASAN WISATA KUTA LOMBOK TENGAH - Jumail, Mohamad (Jurnal Ilmiah Pariwisata, 2012)
This research is descriptive, where the essence isability in displaying “apicture” of tourism phenomenon from the past, the present, to the future. Therefore,qualitative approach is good choice. The respondent are tourists which haddetermined by quote sampling and for the stakeholders determined by purposivesampling. Moreover, the data is gathered by observation, interview, questionnaire,literature review, documentation and focus group discussions which analyzed byqualitative-interpretative and quantitative with Likert scales. Thus, all analysis werepresented in diagram, chart, picture, photo, and narration or statements as well.Based on The tourists image (pre—in site—post) visiting shown a positivetrend, positive image were increasing and decreasing in negative image. Thecomponents of image for international tourist dominated by functional—psychologypatterns, unique—holistic as its attributes. Differs to domestic tourist wherepsychology—functional as the pattern and, the attribute were similar to internationaltourists. Based on image formation, Kuta Lombok Tengah destination mainly formedby organic image, but modified imagery were not significantly contribute. Finally,several aspects which must be put on top priority in terms of tourism imageimprovement are accessibilities, amenities, the cleanliness of the beaches and theaggressively of the hawkers as well